Infrared and Thermal Investigations of Dibenzyl Sulphoxide Complexes of Zinc(II) and Cadmium(II) - Kumar, Pravesh (Asian Journal of Chemistry, 2010)
Dibenzyl sulphoxide (DBzSO) complexes of the formula MX2·4DBzSO (M = Zn or Cd; X ═ Cl, Br, I, NCS or CH3COO) have been prepared and characterized by elemental analysis, molecular conductivity, molecular weight data and IR spectral measurements. TGA and DTA of the complexes were also studied.